Vaginal cervico-isthmic cerclage versus McDonald cerclage in women with a previous failure of prophylactic cerclage: A retrospective study. (September 2017) - Perrine, Capmas; Irène, Letendre; Camille, Leray; Xavier, Deffieux; Laura, Duminil; Damien, Subtil; Hervé, Fernandez
Abstract: Aim: Compare preterm births before 30 weeks of gestation in women with a previous failed McDonald cerclage that benefit from another McDonald cerclage (or simplified Shirodkar cerclage) or a vaginal cervico-isthmic cerclage. Methods: Women with a cerclage performed at the end of the first trimester of a singleton pregnancy with a previous failed prophylactic McDonald cerclage were included in this mutlicenric study involving four teaching hospitals. Comparisons between groups were done using a chi square test and a student t -test. Results: We enrolled130 women, 85 in the vaginal cervico-isthmic cerclage group and 45 in the classic cerclage group. There was no significant difference in the rate of delivery after 30 weeks of gestation (92 versus 93% p = 0.75). However in the cervico isthmic cerclage, women were significantly older, presented more late foetal loss and fewer live children in the cervico-isthmic cerclage group. Rate of antenatal hospitalization andantenatal corticotherapy were significantly higher in the classic cerclage group (69% versus 46%, p < 0.05 and 56% versus 29%, p < 0.05). Conclusions: Rate of delivery before 30 weeks of gestation was not significantly different between the two groups, but women in the vaginal cervico-isthmic cerclage group seem to be at higher risk for late foetal loss or premature delivery. This procedure generates less threatened premature delivery, thus, less hospitalization and antenatal corticotherapy. These arguments are important for women with previous pregnancy loss.